Warning and Response - Muller, V.C. (Scientia Militaria - South African Journal of Military Studies, 2011)
Julian Critchley is the Conservative MP for Aldershot. Although the subtitle of the book reads: ’A study of surprise attack in the 20th century and an analysis of its lessons for the future,’ and although the author illustrates his thesis by citing examples of surprise attack in the various wars since 1939, the essence of this work is concern for the Central European front of NATO. For years, NATO’S plans have been based on the assumption that there would be a period of warning resulting from the deterioration of the international situation and overt activity on the part of the Warsaw Pact forces. Critchley examines the ability of NATO to predict and to respond to the Soviet - Warsaw Pact threat; he believes that NATO’s defence must be credible without reliance upon warning, that warning signs are invariably misinterpreted, disbelieved and filtered by the preconceptions of the politicians. Not even the ability to read the enemy’s codes is a guarantee of learning his intentions. He concludes that the warning of attack is bound to be ambiguous and suggests that in order to prevent war NATO must restore tactical nuclear deterrence in Europe.